Alam yang Bermetafor: Refleksi Bersama Pandemi Covid-19 - Hengki Ario Putra Ginting (FOCUS, 2020)
The plague is not something strange in the story of human civilization. Neverthe- less, the plague has always succeeded in delivering dynamic of humanity to the frightening crisis. At least, in his comment about the pandemic Covid-19, Yuval Noah Harari said that pandemic Covid-19 which we are facing right now has dropped almost all sectors in the world to the most crisis moment in its own generation. It is really possible to say this con- dition is capable enough to make humanity in trouble. It wouldn’t be wrong if we say that “hei..we are in big trouble” or “this pandemic is so terrible” and any expression else, but it would be much more dangerous if we are not capable to realize that pandemic Covid-19 has offered the way and chance for us to create the better future in human civilization. This paper is intended to invite us to reflect this Pandemic Covid-19 from a little bit differ- ent worldview, more precisely we may interpret pandemic Covid-19 as a concrete or real methaphor which explain something unknowable by its own knowable way.